Parasites detected in discus fishes (symphsodon discus) - Nermin Işık; Feyzullah Güçlü; Onur Ceylan (Eurasian Journal of Veterinary Sciences)
This study was carried out to detect the reason of mortalities of 7 Discus fishes (Symphsodon discus) sent to our laboratory. In discus fishes, which death on the 20th day after birth showed pale gills, excess mucus production, lethargic swimming close to the surface, abnormal swimming behavior, balance loss and lethargy. The scrapes of the gills, fins and skin were examined for presence of parasitic fauna under a light microscope. Dactylogyrus sp. (Monogenea), Tetrahymena sp. (Ciliata), Vorticella sp. (Ciliata), Philodina sp. (Metazoa) were identified from all of the examined fishes.